Comparison of chemistry students in solving algorithmic, conceptual and open-ended problems - Abdullah, Wan Nor Azlina Wan; Ab Manaf, Syaida; Mun, Yam Pui; Ibrahim, Nor Hasniza; Surif, Johari; Bunyamin, Abdul Hadi; Nee, Chee Ken (Eclética Química, 2025)
This study analyses students’ achievements level in solving chemistry problems. Questions were designed in algorithm, conceptual and open-ended formats. The limited research on students’ effectiveness in different problem types highlights the need to examine their grasp fundamental chemistry concepts. This research aims to identify and compare achievements levels across the three problems types. A quantitative design using a paper-and-pencil test was employed. The instrument, covering mole concept, acid base, and polymer topics, was administered to 42 high school chemistry students from private school in Johor Bahru through purposive sampling. Descriptive statistics including frequency and percentage, were used to summarize the achievement level. Data were analyzed using SPSS 27.0. Findings shows that open-ended problems recorded the highest low achievement rate (78.6%), compared to algorithmic (9.52%) and conceptual problems (16.7%). These results indicate that open ended problems are the most difficult for students to master, reflecting weaknesses in understanding underlying concepts. Greater emphasis on cultivating problem solving culture in classrooms is recommended.